Peningkatan akurasi passing dengan menggunakan latihan berpasangan pada pemain sepak bola remaja - Marsuna, Marsuna; Rusli, Muhammad; Saman, Abdul (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Passing is one of the fundamental techniques in football. Good passing skills enable players to participate in the game effectively and maintain possession of the ball. Paired short passing drills also help improve individual skills. This research aims to find out whether short passing training in pairs can increase the accuracy of soccer passing in adolescent soccer players. The quantitative method used in the research is a pre-experimental design through one group pretest and posttest. The research instrument used a ball passing accuracy test for 30 seconds and used the short passing practice method in pairs. The population in this study consisted of 20 male Rekminers Club soccer players aged 15-17 years. The sample was selected using a total sampling technique, and the entire population sampled was 20 players. The data analysis technique uses the t-test to test the hypothesis to increase soccer passing accuracy in the pretest and posttest treatment using SPSS version 26. Based on the results of hypothesis testing using the t-test in paired short passing exercises with football passing accuracy ability, there is a significant influence based on pretest and posttest data analysis of 0.000 < 0.05. This exercise was successfully carried out to improve the accuracy of football passing. The research results show that short passing training in pairs is an effective method for improving the passing accuracy of football players.